Removal Methods Assessment Through Reduction Algae Count in Uncovered Water Tank - jassim Al- Mansori, Nesrin; al deen ali klakeel, Saif (International Journal of Engineering and Technology, 2018)
The research includes study the effect of three factors (voltage, rotational speed, acidity) with time to remove or reduce the percentage of algae in uncovered water tank; these factors studied combined with each other or individually. the removal percentage of algae increased by increasing the electrical voltage, Best result of removal was obtained when using two factors, change in the voltage (4, 8,12 and 16) vole /cm and speed of rotation (50, 100, 150 and 200) rpm . The rate of removal of algae was 100% at voltage 16 volts with a rotation speed (200) rpm and 40 min.Â Â  The values extracted for algae removal showed that the best result was (100%) at (voltage 16 vole/cm and acidity with pH 4) with time 30 min. It can be conclude, the best method to remove or reduction of algae in uncovered tanks was physical one as a compared with the other methods like chemical or biological methods. Therefore, it needs additional requirements unlike physical strategies decrease, the cost and time required to evacuate green growth.Â